Meaningful Consultation in Environmental Assessments - Davis, Shelton H.; Rukuba-Ngaiza, Nightingale (World Bank, Washington, DC, 2012)
The World Bank's Operational Directive 4.01 on Environmental Assessments (EA) calls for consulting the public on environmental impacts in Bank-financed projects. The operational directive (OD) requires borrowers to prepare environmental assessments in those categories of projects that have potential significant impact on the environment. The Bank requires that at designated stages of the EA cycle, borrowers conduct meaningful consultations with affected groups and local NGOs. The criteria for assessing meaningful consultation is based on the Borrower's or EA preparer's capacity to identify the affected groups and obtain information. Meaningful consultation will be deemed to have taken place if the final EA document reflects the views of affected groups, local nongovernmental organizations, and those traditionally excluded from the consultative and planning processes, as well as those of the project's sponsor and other relevant government agencies.